Characterization of the roles of amphiregulin and transforming growth factor β1 in microvasculature-like formation in human granulosa-lutein cells - Li, Hui; Chang, Hsun-Ming; Li, Saijiao; Klausen, Christian; Shi, Zhendan; Leung, Peter C.K. (Frontiers in Cell and Developmental Biology, 2022)
Vascular endothelial-cadherin (VE-cadherin) is an essential component that regulates angiogenesis during corpus luteum formation. Amphiregulin (AREG) and transforming growth factor β1 (TGF-β1) are two intrafollicular factors that possess opposite functions in directing corpus luteum development and progesterone synthesis in human granulosa-lutein (hGL) cells. However, whether AREG or TGF-β1 regulates the VE-cadherin expression and subsequent angiogenesis in the human corpus luteum remains to be elucidated. Results showed that hGL cells cultured on Matrigel spontaneously formed capillary-like and sprout-like microvascular networks. Results of specific inhibitor treatment and small interfering RNA-mediated knockdown revealed that AREG promoteed microvascular-like formation in hGL cells by upregulating the VE-cadherin expression mediated by the epidermal growth factor receptor (EGFR)-extracellular signal-regulated kinase1/2 (ERK1/2) signaling pathway. However, TGF-β1 suppressed microvascular-like formation in hGL cells by downregulating VE-cadherin expression mediated by the activin receptor-like kinase (ALK)5-Sma- and Mad-related protein (SMAD)2/3/4 signaling pathway. Collectively, this study provides important insights into the underlying molecular mechanisms by which TGF-β1 and AREG differentially regulate corpus luteum formation in human ovaries.